Lithium composite negative electrode with tab and lithium battery comprising lithium composite negative electrode

By designing a structure with its own electrode in the lithium composite negative electrode of a lithium battery, seamless connection is achieved using the complementary structure between the current collector layer and the electrode, the problem of difficulty in combining the current collector film material and the electrode ear is solved, and the overall performance and production efficiency of the battery are improved.

CN222637306UActive Publication Date: 2025-03-18CHINA ENERGY LITHIUM
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202420287570.2
Authority / Receiving Office
CN · China
Patent Type
Utility models(China)
Current Assignee / Owner
Filing Date
2024-02-07
Publication Date
2025-03-18
Estimated Expiration
2034-02-07

AI Technical Summary

Technical Problem

In existing lithium batteries, the current collector copper foil is difficult to replace the carbonaceous membrane or conductive membrane material directly used in the extreme ear, which leads to difficulties in batch production, and the thickness fluctuates greatly at the joint between the current collector membrane and the extreme ear, affecting the overall performance of the battery.

Method used

A lithium composite negative electrode with its own electrode ear is designed. By forming a complementary structure between the current collector layer and the electrode ear, the electrode ear and the current collector layer are seamlessly connected, solving the problem of combining the current collector film material and the electrode ear.

Benefits of technology

The seamless connection between the current collector film and the pole ear is achieved, ensuring the surface flatness of the battery and the uniformity of the overall thickness, simplifying the production process, and supporting large-scale mass production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN222637306U_ABST
    Figure CN222637306U_ABST
Patent Text Reader

Abstract

The utility model provides a lithium composite negative electrode with a tab and a lithium battery comprising the lithium composite negative electrode. The lithium composite negative electrode comprises an upper negative electrode layer and a lower negative electrode layer, the current collector layer is clamped between the two negative electrode layers, the width of the current collector layer is smaller than that of the negative electrode layers, one end of the current collector layer is aligned with the negative electrode layers in the width direction, and the other end of the current collector layer is provided with a tab joint part; the tab is provided with a current collector layer joint part, the current collector layer joint part and the tab joint part form a complementary structure, and the tab is seamlessly connected with the current collector layer through the complementary structure.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The utility model relates to the technical field of electrochemical energy storage, in particular to a lithium composite negative electrode for a lithium battery. Background Art

[0002] As society's requirements for the energy density of lithium-ion batteries are getting higher and higher, the current research direction is turning to negative electrode materials with higher specific capacity. Metallic lithium is considered to be the best negative electrode material due to its capacity of 3860mAh / g and low potential of -3.04V. In addition, to increase the energy density of the battery, it is necessary to reduce the proportion of inactive substances. For the current collector, although the weight of the current collector copper foil can be reduced by continuously thinning the thickness of the copper current collector, the density of metallic copper is 8.96g / cm 3 , the thinnest 4um thick copper foil (4um thick copper foil is easy to break) is still equivalent to 67um thick lithium metal. Currently, carbon film materials with certain conductivity or other flexible conductive film materials are being developed to replace the current collector copper foil. The density of carbon film materials is 1g / cm 3 It can replace the traditional current collector very well; but the problem is that after the relevant film materials are composited with metal lithium negative electrode, the carbon film materials or other conductive film materials cannot be used directly as pole ears, and the pole ears of the metal foil materials need to be led out for welding and use; and how to lead out the pole ears in batches, and the led-out pole ears and carbon film materials can form a current collector as a whole, and at the same time the thickness fluctuation of the junction of the current collecting film material and the pole ears is not large (less than 5um), which requires special design. Utility Model Content

[0003] In view of the above problems, the utility model provides a lithium composite negative electrode with a self-contained tab.

[0004] The utility model adopts the following technical solutions:

[0005] A lithium composite negative electrode with a self-contained tab, the lithium composite electrode comprising: two upper and lower negative electrode layers; a current collector layer sandwiched between the two negative electrode layers, wherein the width of the current collector layer is smaller than that of the negative electrode layer, one end of the current collector layer is aligned with the negative electrode layer in the width direction, and the other end has a tab joint; and a tab, wherein the tab has a current collector layer joint, the current collector layer joint and the tab joint form a complementary structure, and the tab is seamlessly connected to the current collector layer through the complementary structure.

[0006] In certain embodiments, the tab-joining portion of the current collector layer has a continuously distributed regular shape.

[0007] In certain embodiments, the regular shape includes a rectangle, a triangle, an arc (including a semicircular or nearly circular structure).

[0008] In certain embodiments, the tab engaging portion has a comb-like or sawtooth shape.

[0009] In certain embodiments, the current collector layer joint portion and the tab joint portion form a snap-on structure.

[0010] In certain embodiments, the tab joint portion of the current collector layer has a regularly distributed columnar protrusion or arc-shaped recessed structure, and the top of the columnar protrusion or arc-shaped recess has a flange extending in a direction perpendicular to the thickness direction of the current collector layer (for example, forming a "T"-shaped structure), which can make the combination of the current collector layer and the tab more secure.

[0011] In some embodiments, the current collector joint portion and the tab joint portion form a mortise and tenon structure, making the joint more secure.

[0012] In certain embodiments, the negative electrode layer is a metallic lithium layer or a lithium alloy layer.

[0013] In some embodiments, the current collector film material is a carbon film material or other flexible conductive film material.

[0014] In some embodiments, the tab is made of metal foil.

[0015] In some embodiments, the thickness of the negative electrode layer is 1-100 um and the width is 50-1400 mm;

[0016] In certain embodiments, the thickness of the current collector layer is 5-50 um.

[0017] In certain embodiments, the tab has the same thickness as the current collector layer, and the combined width of the current collector layer and the tab is greater than the width of the negative electrode layer.

[0018] The utility model also provides a lithium battery, which comprises the above-mentioned lithium composite negative electrode with its own pole ear.

[0019] The utility model has at least one of the following advantages:

[0020] (1) The lithium composite negative electrode with its own tabs of the utility model solves the problem of tabs being introduced in the industrial production of current collector film materials (except metal current collectors).

[0021] (2) The lithium composite negative electrode with its own tab of the utility model can obtain a composite negative electrode with a smooth surface because the thickness of the current collector film material and the lead tab foil material are consistent, and the overall thickness uniformity of the negative electrode is good.

[0022] (3) The production process of lithium composite negative electrodes with built-in tabs is simple and can be mass-produced. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 Schematic diagram of the complementary style of the current collector layer and the pole ear of the utility model Figure 1 (Rectangular regular shapes are complementary).

[0024] Figure 2 Schematic diagram of the complementary style of the current collector layer and the pole ear of the utility model Figure 2 (Semicircle regular shapes are complementary).

[0025] Figure 3 Schematic diagram of the complementary style of the current collector layer and the pole ear of the utility model Figure 3 (Regular shapes close to circles are complementary).

[0026] Figure 4 Schematic diagram of the complementary style of the current collector layer and the pole ear of the utility model Figure 4 (Triangle regular shapes are complementary).

[0027] 1-current collector layer, 2-ear DETAILED DESCRIPTION

[0028] In order to make the purpose, technical solution and advantages of the utility model more clear, the specific implementation of the utility model is described in detail below with reference to the accompanying drawings. It should be understood that the technical features involved in each implementation described below can be combined with each other as long as they do not conflict with each other.

[0029] One aspect of the utility model provides a lithium composite negative electrode with a self-contained tab, comprising: two upper and lower negative electrode layers; a current collector layer and a tab sandwiched between the two negative electrode layers, wherein the width of the current collector layer is smaller than the width of the negative electrode layer, one end of the current collector layer is aligned with the negative electrode layer in the width direction, and the other end has a tab joint; the tab has a current collector layer joint, the current collector layer joint and the tab joint form a complementary structure, and the tab is seamlessly connected to the current collector layer through the complementary structure.

[0030] Figures 1 to 4 Four representative complementary styles of the current collector layer and the tab in the present invention are shown, among which Figure 1 The tab joint portion of the current collector layer 1 has a rectangular regular shape (comb-like structure), and the tab 2 has a structure complementary thereto; Figure 2 , Figure 3 The tab joint portion of the current collector layer 1 has an arc shape (semicircular or nearly circular structure), and the tab 2 has a complementary structure thereto; Figure 4 The tab joint portion of the current collector layer 1 has a triangular regular shape (sawtooth structure), and the tab 2 has a structure complementary thereto.

[0031] In the lithium composite negative electrode of the utility model, the negative electrode layer (active material) is made of metallic lithium or lithium alloy, the film material of the current collector layer is made of carbon film material or other flexible conductive film material; the tab is made of metal foil material.

[0032] According to one embodiment, the active material can be distributed to the current collector layer and a portion of the tab area through coating, pressure lamination, and vapor deposition processes to obtain a double-sided lithium composite negative electrode with its own tabs.

[0033] According to one embodiment, the thickness of the active material metal lithium or lithium alloy (thickness of the negative electrode layer) can be 1-100 um, preferably 1-20 um; the width is 50-1400 mm, preferably 200-700 mm.

[0034] According to one embodiment, the lithium alloy is formed by a combination of metallic lithium and any one or at least two elements of Ag, Au, Sn, Si, Zn, Al, Mg, In, Ga, B, Mn, Sb, Bi, Cr, C, V, Cu, Fe or Ti.

[0035] According to one embodiment, the thickness of the current collector layer is 5-50 um, preferably 5-20 um.

[0036] According to one embodiment, the tab is made of metal foil, including copper foil, nickel foil, stainless steel foil; the thickness of the metal foil is 5-50um, preferably 5-20um, and the thickness of the tab is matched or consistent with the thickness of the current collector film. The width of the tab can be 10-40mm.

[0037] According to one embodiment, the edge region of the current collector layer and the edge region of the tab can be respectively formed into a continuous regular complementary pattern by using 3D printing technology, mold punching technology, laser etching technology, etc. The width of the complementary region can be 2-15 mm.

[0038] According to one embodiment, the complementary patterns of the edge of one side of the current collector layer and the edge of one side of the tab may include: arc-like, semicircular, circular, rectangular or square, triangular, or S-shaped.

[0039] According to one embodiment, the lithium composite negative electrode with its own tab can be in the form of a continuous web (rolled), wherein the edge area on one side of the current collector layer and the edge area on one side of the tab are respectively formed into complementary structures by laser etching technology, and then the current collector film material and the tab are continuously unrolled. After the initial debugging of several meters to more than ten meters, the edge of one side of the current collector film material and the edge of one side of the tab can be well matched together, and there is no gap between the two materials. In addition, the thickness of the current collector film material and the tab foil material are consistent. In this way, the current collector film material and the tab become one.

[0040] The lithium composite electrode can be prepared by the following method, which comprises:

[0041] One side edge of the current collector film material and one side edge of the metal foil material of the lead-out tab are formed into complementary patterns respectively by means of 3D printing technology, specific mold punching technology, and laser etching technology.

[0042] First, unwind the current collector film material in the middle position and the metal foil material for the lead-out tab. Through debugging, the edge of one side of the current collector film material and the edge of one side of the metal foil material for the lead-out tab are completely matched together; then unwind the upper and lower rolls of lithium strip or lithium alloy strip. The unwinding speed of the current collector film material, metal foil and metal lithium strip or lithium alloy strip is consistent, and the unwinding speed is 5-50 m / min.

[0043] The upper and lower rolls of metal lithium strips or lithium alloy strips, the current collector film material and the metal foil material in the middle are pressure-compounded to obtain a composite negative electrode with its own tabs.

[0044] Another aspect of the utility model provides the use of the composite negative electrode with a self-contained tab in a lithium-ion battery.

[0045] According to one embodiment, the lithium battery comprises the above-mentioned lithium composite negative electrode, and the positive electrode material is selected from ternary nickel-cobalt-manganese material, ternary nickel-cobalt-aluminum material, lithium-rich manganese-based positive electrode material, lithium cobalt oxide, lithium iron phosphate, and sulfur-based positive electrode material.

[0046] According to one embodiment, the electrolyte of the lithium battery can be selected from a liquid electrolyte or a solid electrolyte; the liquid electrolyte can be selected from an ester or an ether; the solid electrolyte can be selected from a halide solid electrolyte, an oxide solid electrolyte, a sulfide solid electrolyte, a polymer electrolyte or an organic-inorganic mixed electrolyte, such as a polyethylene oxide (mixed oxide, halide or sulfide powder) electrolyte.

[0047] For liquid batteries, the diaphragm is made of polypropylene (PP), polyethylene (PE) or a PP and PE laminated diaphragm, and the diaphragm can be coated with ceramic or polyvinylidene fluoride.

[0048] The battery style can be square, soft pack or cylindrical.

[0049] The present invention is illustrated below by way of examples. The various product structural parameters, various reaction participants and process conditions used in the following examples are all relatively typical examples. However, after a large number of experiments and verifications by the inventor of this case, other different structural parameters, other types of reaction participants and other process conditions listed above are also applicable and can also achieve the technical effects claimed in this utility model.

[0050] Example 1

[0051] Using 3D printing technology, a semicircular shape is first printed on one edge of the rolled carbon nanotube film as the current collector, and then a semicircular shape is printed on one edge of the other roll as the tab copper foil. The diameter of the semicircle is 0.5 cm, and the shapes of the two edges can complement each other to form a complete whole.

[0052] First, unwind the carbon nanotube film (thickness 10um) of the current collector film in the middle position and the copper foil (thickness 10um) of the metal foil for the pole ear, and wait until the edges of the carbon nanotube film and the copper foil overlap as a whole, and then unwind the upper and lower rolls of metal lithium tape. The thickness of the lithium tape is 20um, the widest width of the carbon nanotube film is 150mm, the widest part of the copper foil is 20mm, and the width of the lithium tape is 152mm. The semicircular depression on one edge of the carbon nanotube film and the semicircular protrusion on one edge of the copper foil complement each other to form a complete whole. The unwinding speed of the carbon nanotube film, copper foil and metal lithium tape is consistent, and the unwinding speed is 10 meters / min. The three layers of tape are pressure-compounded to obtain a lithium composite negative electrode with a pole ear. The thickness consistency of the lithium composite negative electrode is good, and the thickness deviation of the entire negative electrode surface is less than or equal to 3um.

[0053] Example 2

[0054] Using 3D printing technology, an equilateral triangle shape is first printed on one edge of the rolled current collector graphite film, and then an equilateral triangle shape is printed on one edge of the other roll of the tab copper foil. The height of the equilateral triangle is 0.4 cm, and the shapes of the two edges can complement each other to form a complete whole.

[0055] First, unwind the current collector graphite film (thickness 15um) in the middle position and the metal foil copper foil (thickness 15um) for the pole ear. Wait until the edges of the graphite film and the copper foil overlap as a whole, and then unwind the upper and lower rolls of lithium-magnesium alloy strips (magnesium content is 5%). The thickness of the lithium alloy strip is 20um, the widest width of the graphite film is 120mm, the widest part of the copper foil is 20mm, and the width of the lithium strip is 122mm. The triangle on one edge of the graphite film and the triangle on one edge of the copper foil complement each other to form a complete whole. The unwinding speed of the graphite film, copper foil and lithium-magnesium alloy strip is consistent, and the unwinding speed is 8 meters / min. The three layers of strips are pressure-compounded to obtain a lithium composite negative electrode with a pole ear. The thickness consistency of the lithium composite negative electrode is good, and the thickness deviation of the entire negative electrode surface is less than or equal to 3um.

[0056] Comparative Example 1:

[0057] Two rolls of lithium metal tape are unwound at the same time, the thickness of the lithium metal tape is 20um, and the carbon nanotube film (thickness 10um) of the current collector film in the middle position and the copper foil (thickness 10um) of the pole ear are unwound at the same time. The width of the carbon nanotube film is 150mm, the width of the copper foil is 20mm, and the width of the lithium metal tape is 152mm. The edge of one side of the carbon nanotube film and the edge of one side of the copper foil overlap together, the overlapping area is 1mm, and the thickness of the overlapping area is 12um thicker than the thickness of the non-overlapping area. The unwinding speed of the carbon nanotube film, copper foil and lithium metal tape is consistent, and the unwinding speed is 6 meters / min. The three-layer tape is pressure-compounded to obtain a lithium composite negative electrode with its own pole ear.

[0058] Embodiment 3:

[0059] The negative electrode used the lithium composite negative electrode prepared in Example 1, and the positive electrode used NCM (811 nickel-cobalt-manganese ternary positive electrode), with a coating surface density of 50 mg / cm 2 The positive electrode sheet area is 43*56mm, the negative electrode sheet area is 45*58mm, and the PE material separator is used to assemble a 4-positive and 5-negative soft-pack battery. The electrolyte uses 1M LiPF6, EC (ethylene carbonate): EMC (ethyl methyl carbonate) = 3:7 (vol / vol). The negative electrode sheet, NCM ternary positive electrode sheet and separator are assembled into a soft-pack battery with the help of a stacking machine. The aluminum-plastic pit depth is 2mm. The laminated soft-pack battery cell is easy to fill into the aluminum-plastic pit, and there are no problems with subsequent processes. The test voltage range is 2.8-4.4V, the charging current is 0.1C, and the discharge current is 0.5C.

[0060] Comparative Example 2:

[0061] The negative electrode uses the lithium composite negative electrode of comparative example 1, and the assembly of the positive electrode, separator, electrolyte and soft-pack battery is consistent with that of Example 3. Since the thickness of the splicing of the lithium composite negative electrode is 12um thicker than that of other areas, the thickness of the splicing of the 5 negative electrodes will be 60um thicker. When the pit is 2mm deep, the pole piece at the splicing cannot be packaged. Due to the local thickness difference, it is necessary to replace the aluminum-plastic pit with a thicker pit depth for packaging; when it is replaced with an aluminum-plastic pit with a deeper pit depth, most of the pole pieces (excluding the splicing) are suspended in the aluminum-plastic pit. When vacuum packaging is performed, the edge area around the aluminum-plastic pit will be severely bent, and there is a risk of leakage.

[0062] It should be understood that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A lithium composite negative electrode with a self-contained tab, characterized in that: The lithium composite negative electrode comprises: Two negative electrode layers: upper and lower; A current collector layer sandwiched between two negative electrode layers, wherein the width of the current collector layer is smaller than that of the negative electrode layer, one end of the current collector layer is aligned with the negative electrode layer in the width direction, and the other end of the current collector layer has a tab joint portion; and The pole tab has a current collector layer joint portion, the current collector layer joint portion and the pole tab joint portion form a complementary structure, and the pole tab is seamlessly connected to the current collector layer through the complementary structure.

2. The lithium composite negative electrode with a self-contained tab according to claim 1, characterized in that: The tab joints of the current collector layer have a continuously distributed regular shape.

3. The lithium composite negative electrode with a self-contained tab according to claim 2, characterized in that: The regular shapes include rectangles, triangles, and arcs.

4. The lithium composite negative electrode with a self-contained tab according to claim 2, characterized in that: The tab engaging portion has a comb-like or sawtooth-like shape.

5. The lithium composite negative electrode with a tab according to claim 1, characterized in that: The current collector layer joint portion and the tab joint portion form a snap-on structure.

6. The lithium composite negative electrode with a tab according to claim 1, characterized in that: The tab joint portion of the current collector layer has a regularly distributed columnar protrusion or arc-shaped depression structure, and the top of the columnar protrusion or arc-shaped depression has a flange extending in a direction perpendicular to the thickness direction of the current collector layer.

7. The lithium composite negative electrode with a tab according to claim 1, characterized in that: The negative electrode layer is a metal lithium layer or a lithium alloy layer.

8. The lithium composite negative electrode with a tab according to claim 1, characterized in that: The thickness of the negative electrode layer is 1-100 um and the width is 50-1400 mm; The thickness of the current collector layer is 5-50 um.

9. The lithium composite negative electrode with a self-contained tab according to claim 1, characterized in that: The electrode tab has the same thickness as the current collector layer, and a total width of the current collector layer and the electrode tab is greater than a width of the negative electrode layer.

10. A lithium battery, characterized in that: The lithium battery comprises the lithium composite negative electrode with a self-contained tab according to any one of claims 1 to 9.